THE DELUTION OF A MAN WHO IS NOT CONSIDERED AS A BELOVED ONE TO HIS LOVER IN JEAOLUS SONG’S BY LABRINTH - priyoto Priyoto; Ikbal Ramadhan (STIBA IEC JAKARTA, 2020)
The objective of this study are: 1) to analyze the literal meaning and the figurative language in the lyrics of the jealous song; 2) to know the reflection of having excessive delusion based on the lyrics; and 3) to describe the emotional feelings of the speaker that implied on the lyric jealous song. This song tells about a man that once had a girlfriend but he lost her and cannot stand the fact that she is giving her love to someone else. He also feels jealous of all things around her, because they are closer than he could ever be. To analyze this song the writer uses psychological approach. In the society there is someone who has the same feeling or experience that is implied from this song, and gives influence to people’s mindset. The mindset is directed with the intension that the people get the impression after listening and reading the lyrics. This song gives reaction delusion to be self defense mechanism and the anxiety disorder. Denial, compensation, displacement, identification, repression and emotional quantity become factors which give contribution to Labrinth in implied his delusion.